Pengaruh Suhu Mesin Pembuat Filamen 3D Printing Dari Kemasan Mineral Terhadap hasil Filamen Menggunakan Uji Tarik - Esya Abinda, Azora; Rollastin, Boy; Pristiansyah, Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to examine the effect of machine temperature on the process of making 3D printing filament from recycled plastic water bottles on filament quality, focusing on tensile testing as the main mechanical parameter. The filament produced from recycled PET (Polyethylene Terephthalate) plastic bottles is used in 3D printing, representing an approach to reduce plastic waste. The filament-making machine's temperature is considered a significant variable that can influence the mechanical properties of the produced filament, including tensile strength. In this study, the Taguchi L4 method was employed, resulting in 12 test specimens with varying machine temperatures (210°C and 220°C), pulling speed (18 RPM and 24 RPM), nozzle temperature (260°C), bed temperature (90°C), print speed (50%), and infill density (107.1%). The results showed that the optimum outcome was achieved in the third experiment, with a combination of 220°C machine temperature and 18 RPM pulling speed, with an average tensile strength of 59.6 MPa. This study contributes to optimizing the process parameters for making 3D printing filaments from plastic water bottles.